Dynamic Optimal Capital Structure and Technological Change - Hans Lööf (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
This paper incorporates the cost of adjustment between observed and optimal leverage in explaining the variation in firm?s equity or bank-debt financing investments. Using a dynamic adjustment approach identifies the determinants to capital structure between different financial systems. In relation to firm sales U.K and U.S firms have 50-100 percent more equity financing than Swedish firms depending on which measure used, while the ratio of debt to sales is highest in Sweden. The major findings are that observed leverage often deviates from the target leverage in both equity and debt dominated systems. There are large and also unexpected crosscountry differences in determinants to optimal capital structure. Swedish and U.K. firms deviate more from the optimal level than U.S firms. A faster speed towards the target is observed in the equity based systems.
Keywords: O31; G32; O16; C51; C23; 330; Capital structure; dynamic adjustment; panel data; optimal leverage; financial markets; cross-country comparison; technological change; Kapitalstruktur; Bankensystem; Risikokapital; Innovation; Technischer Fortschritt; Schätzung; Schweden; Großbritannien; Vereinigte Staaten